Crisis económica y reformas fiscales en Centroamérica - Menkos Zeissig, Jonathan (Revista Española de Desarrollo y Cooperación, 2023)
The global economic crisis has changed the view of fiscal policy in Central America. The fall of the economic activity in the region as a result of its strong links with the outside, has opened the possibility of implementing anti-crisis plans that could shield the social spending and tax reforms that improved tax collection, but also sought to move towards a progressive overall tax policy. With the exception of Costa Rica, all countries that approved tax reforms will have significant benefits in collection if there is a strengthening of tax administrations. The outstanding challenges in tax matters must be observed from a political perspective, where it must continuing to seek consensus to advance into a related fiscal agenda, among others, with the reduction in tax liens, assessment of public expenditure and transparency.